Implantação de um programa de manutenção baseado em confiabilidade na mineração - Silva, Wagner de Castro Alves e (2017)
The proposed study aims to create a reliability program for Tubarão Port Terminal controlled by Vale. Initially, the paper presents Vale's mining scenario until 2016 and the strategic position of the Tubarão Terminal. From the reading of the scenario of the Terminal and the changes that took place inside, the biannual strategic planning was presented, which would support the maintenance for the coming years. In parallel, the backbone of a 9-step reliability program was created. The 130 initiatives of the 11 strategic objectives of goal planning were distributed throughout these 9 implementation stages, which would raise the reliability level of the plant to optimum levels of availability and cost reduction. Therefore, the work created biannual strategic planning, the implementation stages of the reliability program, map of indicators, training, catalog of short-, medium- and long-term reliability products, map of areas of reliability, examples of applications in various areas and ultimately an asset tracking center structured on the basis of the concept of integrated inspection.